Pengaruh E-Service Quality Dan Kemudahan Aplikasi PLN Mobile Terhadap Kepuasan Pelanggan (Pada Unit Layanan Pelanggan PLN Metro) - Wahid, Nurdin; Ratmono, Ratmono (Jurnal Manajemen DIVERSIFIKASI, 2022)
ABSTRACT NURDIN WAHID. A, 2021, "The Effect of E-Service and the Ease of the PLN MobileApplication on Customer Satisfaction". Faculty of Economics and Business,UniversitasMuhammadiyah Metro. Advisors: (1) Ratmono, S.E., M.M and Advisors: (2)Nani Septiana, S.E., M.M. This study aims to determine the effect of e-service quality and convenience as auser of the PLN Mobile ULP Metro application. With the technique of data collectingnamely accidental sampling with a sampling time of 30 days obtained as many as 97sample. In this study, the method used is explanatory researchwith a quantitativeapproach, namely interviews, correspondences, and questionnaires. In this study, theanalytical tool used is multiple linear regression analysis.The determination of thedependent and independent variables were processed with the computer program SPSSVersion 16 For Windows. The results of research that have been conducted by researchers show aninfluence of E-Service Quality and the ease of the PLN Mobile application on customersatisfaction of ULP Metro. Based on the results of the analysis, the data obtained is Fcount 46,857> 3.09, which is shown by linear regression with a coefficient ofdetermination (R2) 0.499. The effect of e-service quality and convenience is 49.9% canbe explained by customer satisfaction variables and the other 50.1% is influenced orexplained by other variables not discussed in this study. Keywords: E-Service Quality, Ease, customer satisfaction, PLN MOBILE